2022
DOI: 10.1177/17534666221081047
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, seasonal variation, and susceptibility to acute exacerbation of COPD in the pandemic year: a nationwide population study

Abstract: Background: Previous studies have suggested that the coronavirus disease 2019 (COVID-19) pandemic was associated with a decreased rate of acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Data on how the COVID-19 pandemic has influenced mortality, seasonality of, and susceptibility to AECOPD in the chronic obstructive pulmonary disease (COPD) population is scarce. Methods: We conducted a national population-based retrospective study using data from the Health Insurance Institute of Slovenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 42 publications
(67 reference statements)
3
40
0
Order By: Relevance
“…A reduction in hospitalizations for AECOPD during the first months of the pandemic has been documented in the literature, with estimates ranging from -42% to -48% among nationwide studies. 68,15,17 In this study, we show that this phenomenon persisted far beyond the first pandemic wave, with a global decline of -35% hospital admissions when considering the whole 2020-2021 pandemic years, and nearly 60,000 fewer stays than expected in the absence of a pandemic. In contrast, hospitalizations for causes other than COVID-19 reduced by only 13% in France in 2020 compared to 2019, 23 indicating that the decline was steeper for AECOPD-related hospitalizations.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…A reduction in hospitalizations for AECOPD during the first months of the pandemic has been documented in the literature, with estimates ranging from -42% to -48% among nationwide studies. 68,15,17 In this study, we show that this phenomenon persisted far beyond the first pandemic wave, with a global decline of -35% hospital admissions when considering the whole 2020-2021 pandemic years, and nearly 60,000 fewer stays than expected in the absence of a pandemic. In contrast, hospitalizations for causes other than COVID-19 reduced by only 13% in France in 2020 compared to 2019, 23 indicating that the decline was steeper for AECOPD-related hospitalizations.…”
Section: Discussionmentioning
confidence: 59%
“…However, this assumption is not supported by nationwide studies from Denmark and Slovenia, where all-cause mortality was reported to decrease in COPD patients, regardless of severity. 7,8 Our second major finding is a 24% increase in the proportion of in-hospital deaths for AECOPD stays during the pandemic, with nearly 2,000 estimated excess deaths. There could be several reasons for this observation.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations